La nouvelle politique de population de la République islamique : enjeux et défis - Marie Ladier-Fouladi (Bulletin de l’Association de Géographes Français)
Iran has experienced two demographic policies to reduce its population growth, under the imperial regime and under the Islamic Republic. While the first did not even reach its minimum goals, the second was very successful. The fertility decreased by 70 % in only 17 years, dropping from 6.4 children per women in 1986 to 2.3 in 2003. However this demographic revolution has been the consequence of the evolution of society more than state policies. Since 2009, the government and conservative forces have adopted a populationist policy to bring the population of Iran to 150 million on the close horizon. The analysis of the dynamics of Iranian demography shows that this goal is utopian but probably hides ideological and political objectives to counter current social openness, and to assert Iran’s demographic and geopolitical weight in the region by offsetting low fertility by an unprecedented immigration policy.